Comparing the Effectiveness of Schema Therapy and Mindfulness-Based Stress Reduction Program on Sexual Satisfaction in Married Individuals - Salari, Tahereh; Nasrollahi, Bita; Ghorban Jahromi, Reza (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present research aimed to compare the effectiveness of schema therapy and a mindfulness-based stress reduction program on sexual satisfaction among married individuals. Method: This quasi-experimental study employed a pretest-posttest design with a one-month follow-up and included a control group. The study population consisted of all married individuals with marital issues who visited the Khodbidari Psychological Center in the first half of 2019, totaling approximately 180 individuals. From this group, 45 individuals were selected through purposive sampling and randomly assigned to three groups of 15. The experimental groups underwent 8 sessions of 90-minute schema therapy by Young et al. (2003) and the mindfulness-based stress reduction program by Kabat-Zinn (2003), while no intervention was performed for the control group. The data collection tool was the Sexual Satisfaction Scale (Larson et al., 1998). The data were analyzed using SPSS software version 21 and repeated measures ANOVA. Findings: The results indicated that there was a significant difference in sexual satisfaction scores among the groups (p = 0.001, F = 21.58), and both schema therapy and the mindfulness-based stress reduction program increased sexual satisfaction among married individuals. Furthermore, there was no significant difference between the two groups in this regard (p < 0.05). Conclusion: According to the results, both schema therapy and the mindfulness-based stress reduction program can be used to improve sexual satisfaction in married individuals.